Anode materials and solid batteries

By using a composite alloy composed of Li single-phase and Li-M alloy phase as the negative electrode material, the problem of the Li metal anode easily deactivated in a dry atmospheric atmosphere is solved, and a high capacity maintenance rate in an oxygen-containing gas atmosphere is achieved.

CN114335498BActive Publication Date: 2025-03-28TOYOTA JIDOSHA KK
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202111111532.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2020-09-30
Filing Date
2021-09-23
Publication Date
2025-03-28
Estimated Expiration
2041-09-23

AI Technical Summary

Technical Problem

The Li metal negative electrode is prone to inactivate due to nitriding and oxidation in a dry atmospheric atmosphere, resulting in a low capacity maintenance rate of solid batteries.

Method used

A composite alloy composed of Li single phase and Li-M alloy phase is used as the negative electrode material, where M is selected from Al, In and Zn, and the content ratio of M is 0.90% by mass or more and 21.00% by mass or less to form a film and suppress reaction with the atmosphere.

Benefits of technology

Even if exposed to an oxygen-containing gas atmosphere, it is difficult to inactivate the negative electrode material, which improves the capacity maintenance rate of the solid battery.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN114335498B_ABST
    Figure CN114335498B_ABST
Patent Text Reader

Abstract

The present invention relates to a negative electrode material and a solid battery. The purpose is to provide a negative electrode material that is difficult to deactivate even when exposed to an oxygen-containing gas atmosphere and a solid battery using the same. The negative electrode material is a negative electrode material for a solid battery that uses the precipitation-dissolution reaction of lithium metal as a negative electrode reaction, characterized in that the negative electrode material is a composite alloy composed of a Li single phase and a Li-M alloy phase, and the M contained in the Li-M alloy phase is a metal selected from at least one of Al, In and Zn, and the content ratio of the M in the composite alloy is 0.90 mass% or more and 21.00 mass% or less.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to negative electrode materials and solid batteries. Background Art

[0002] With the rapid popularization of information-related devices and communication devices such as personal computers, video cameras and mobile phones in recent years, the development of batteries used as their power sources has received attention. In addition, the automotive industry is also developing high-output and high-capacity batteries for electric vehicles and hybrid vehicles.

[0003] Among batteries, lithium secondary batteries use lithium, which has the highest ionization tendency among metals, as the negative electrode. Therefore, the potential difference with the positive electrode is large, and a high output voltage can be obtained, and thus they have attracted attention in this respect.

[0004] In addition, solid batteries are attracting attention in that a solid electrolyte is used as an electrolyte between a positive electrode and a negative electrode instead of an electrolytic solution containing an organic solvent.

[0005] Patent Document 1 discloses a negative electrode for an all-solid-state secondary battery, which is characterized by comprising a coating layer that covers a negative electrode current collector and allows metal lithium to be deposited through a lithium alloy layer during charging.

[0006] Patent Document 2 discloses a solid battery using Li or a Li alloy for a negative electrode and LAGP for a solid electrolyte.

[0007] Prior art literature

[0008] Patent Literature

[0009] Patent Document 1: Japanese Patent Application Publication No. 2018-129159

[0010] Patent Document 2: Japanese Patent Application Publication No. 2020-009619 Summary of the invention

[0011] Problems to be solved by the invention

[0012] Li metal negative electrode has high energy density, so solid batteries using it are expected as the next generation of vehicle batteries. On the other hand, Li has the lowest redox potential, so it has high reactivity with the atmosphere. Li metal is easily deactivated by nitridation and oxidation even in a dry atmosphere, and the capacity retention rate of solid batteries using it as negative electrode is low. If nitrided Li is generated on the surface of Li metal, the surface of Li metal cracks, and then the deactivation of Li metal proceeds to the inside of Li metal.

[0013] The present disclosure has been made in view of the above-mentioned actual situation, and a main object of the present disclosure is to provide a negative electrode material that is difficult to be deactivated even when exposed to an oxygen-containing gas atmosphere, and a solid battery using the same.

[0014] Means for solving problems

[0015] The negative electrode material disclosed in the present invention is a negative electrode material for a solid battery that utilizes the precipitation-dissolution reaction of lithium metal as the negative electrode reaction, and is characterized in that the negative electrode material is a composite alloy composed of a Li single phase and a Li-M alloy phase, the M contained in the Li-M alloy phase is a metal selected from at least one of Al, In and Zn, and the content ratio of the M in the composite alloy is greater than 0.90 mass % and less than 21.00 mass %.

[0016] In the negative electrode material of the present disclosure, the composite alloy may include 0.25 atomic % or more and 6.10 atomic % or less of Al as the M.

[0017] In the negative electrode material of the present disclosure, the composite alloy may include 0.06 atomic % or more and 1.50 atomic % or less of In as the M.

[0018] In the negative electrode material of the present disclosure, the composite alloy may include 0.10 atomic % or more and 1.20 atomic % or less of Zn as the M.

[0019] The solid battery disclosed in the present invention is a solid battery that utilizes the precipitation-dissolution reaction of lithium metal as a negative electrode reaction, and is characterized in that it comprises: a positive electrode comprising a positive electrode layer, a negative electrode comprising a negative electrode collector and a negative electrode layer, and a solid electrolyte layer arranged between the positive electrode layer and the negative electrode layer, wherein the negative electrode layer comprises a negative electrode material, and the negative electrode material is a composite alloy composed of a Li single phase and a Li-M alloy phase, and the M contained in the Li-M alloy phase is a metal selected from at least one of Al, In and Zn, and when the solid battery is fully charged, the content ratio of the M in the composite alloy is greater than 0.90 mass % and less than 21.00 mass %.

[0020] Effects of the Invention

[0021] The present disclosure can provide a negative electrode material that is difficult to deactivate even when exposed to an oxygen-containing gas atmosphere, and a solid battery using the same. BRIEF DESCRIPTION OF THE DRAWINGS

[0022] Figure 1 This is the Li-Al phase diagram.

[0023] Figure 2 This is the Li-In phase diagram.

[0024] Figure 3 This is the Li-Zn phase diagram.

[0025] Figure 4 This is a schematic cross-sectional view showing an example of the solid battery of the present disclosure.

[0026] Figure 5 This is an example of a discharge curve of the evaluation battery C of Example 3 using a Li-Al composite alloy as the negative electrode.

[0027] Figure 6 This is an example of a discharge curve of the evaluation battery F of Example 6 using the Li-In composite alloy as the negative electrode.

[0028] Figure 7 This is an example of a discharge curve of the evaluation battery H of Example 8 using the Li-Zn composite alloy as the negative electrode. DETAILED DESCRIPTION

[0029] 1. Anode material

[0030] The negative electrode material disclosed in the present invention is a negative electrode material for a solid battery that utilizes the precipitation-dissolution reaction of lithium metal as the negative electrode reaction, and is characterized in that the negative electrode material is a composite alloy composed of a Li single phase and a Li-M alloy phase, the M contained in the Li-M alloy phase is a metal selected from at least one of Al, In and Zn, and the content ratio of the M in the composite alloy is greater than 0.90 mass % and less than 21.00 mass %.

[0031] In the present disclosure, the so-called lithium secondary battery refers to a battery that uses at least one of metallic lithium and lithium alloy as a negative electrode active material and utilizes the precipitation-dissolution reaction of metallic lithium as a negative electrode reaction. In addition, in the present disclosure, the so-called negative electrode refers to a negative electrode including a negative electrode layer.

[0032] In the present disclosure, the term "fully charged" refers to a state of charge (SOC) of the solid battery of 100%. SOC represents the ratio of the charge capacity to the full charge capacity of the battery, and the full charge capacity is SOC 100%.

[0033] The SOC can be estimated from, for example, the open circuit voltage (OCV) of the solid battery.

[0034] The present disclosure can provide a negative electrode material that is difficult to deactivate even when exposed to an oxygen-containing gas atmosphere, and a solid battery using the same.

[0035] In the negative electrode material disclosed herein, at least one metal selected from Al, In and Zn dissolved in a small amount in Li metal forms a film on the surface of Li metal, inhibiting reaction with the atmosphere. Therefore, it is difficult to deactivate even when exposed to an oxygen-containing gas atmosphere. The capacity retention rate of a solid battery using the negative electrode material disclosed herein is high.

[0036] The negative electrode material is a composite alloy consisting of a Li single phase and a Li-M alloy phase.

[0037] M contained in the Li-M alloy phase is at least one metal selected from Al, In and Zn. In the composite alloy, a Li single phase and a Li-M alloy phase (M is at least one phase selected from Al, In and Zn) are precipitated. Whether it is a composite alloy can be determined by comparing the atomic % of the metal contained in the composite alloy with the phase diagram.

[0038] Figure 1 This is the Li-Al phase diagram.

[0039] Figure 2 This is the Li-In phase diagram.

[0040] Figure 3 This is the Li-Zn phase diagram.

[0041] The content of M in the composite alloy is 0.90 mass % or more and 21.00 mass % or less. Furthermore, if it is less than 0.90 mass %, the composite alloy becomes easily deactivated when exposed to an oxygen-containing gas atmosphere. On the other hand, if it exceeds 21.00 mass %, the energy density of the solid battery decreases.

[0042] The composite alloy may contain 0.25 atomic % to 6.10 atomic % both inclusive of Al as M. This corresponds to a content of Al in the composite alloy of approximately 0.96 mass % to 20.16 mass % both inclusive.

[0043] The composite alloy may contain 0.06 atomic % to 1.50 atomic % In as M. This corresponds to a content of In in the composite alloy of about 0.99 mass % to 20.02 mass %.

[0044] The composite alloy may contain 0.10 atomic % to 1.20 atomic % both inclusive of Zn as M. This corresponds to a Zn content in the composite alloy of approximately 0.93 mass % to 10.27 mass % both inclusive.

[0045] Mass % of metal M = {(molecular weight of M) × atomic % of M} ÷ {(molecular weight of Li) × (100 - atomic % of M) + (molecular weight of M) × atomic % of M} × 100

[0046] Among them, the molecular weight of Li can be set to 6.941 g / mol, the molecular weight of Al can be set to 26.98 g / mol, the molecular weight of In can be set to 114.818 g / mol, and the molecular weight of Zn can be set to 65.38 g / mol.

[0047] 2. Solid-state batteries

[0048] The solid battery disclosed in the present invention is a solid battery that utilizes the precipitation-dissolution reaction of lithium metal as a negative electrode reaction, and is characterized in that it comprises: a positive electrode comprising a positive electrode layer, a negative electrode comprising a negative electrode collector and a negative electrode layer, and a solid electrolyte layer arranged between the positive electrode layer and the negative electrode layer, wherein the negative electrode layer comprises a negative electrode material, and the negative electrode material is a composite alloy composed of a Li single phase and a Li-M alloy phase, and the M contained in the Li-M alloy phase is a metal selected from at least one of Al, In and Zn, and when the solid battery is fully charged, the content ratio of the M in the composite alloy is greater than 0.90 mass % and less than 21.00 mass %.

[0049] Figure 4 This is a schematic cross-sectional view showing an example of a fully charged solid state battery of the present disclosure.

[0050] like Figure 4 As shown in FIG. 1 , the solid battery 100 includes a negative electrode current collector 11 , a solid electrolyte layer 12 , a positive electrode layer 13 , and a positive electrode current collector 14 in this order, and includes a negative electrode layer 15 between the negative electrode current collector 11 and the solid electrolyte layer 12 .

[0051] [negative electrode]

[0052] The negative electrode includes a negative electrode current collector and a negative electrode layer.

[0053] [Negative electrode current collector]

[0054] The material of the negative electrode collector may be a material that does not alloy with Li, for example, SUS, copper, and nickel can be listed. As the form of the negative electrode collector, for example, foil and plate can be listed. There is no particular limitation on the top view shape of the negative electrode collector, for example, a circle, an ellipse, a rectangle, and any polygon can be listed. In addition, the thickness of the negative electrode collector varies depending on the shape, for example, it can be in the range of 1 μm to 50 μm, and can be in the range of 5 μm to 20 μm.

[0055] [Negative electrode layer]

[0056] The negative electrode layer contains a negative electrode material, which is a composite alloy consisting of a Li single phase and a Li—M alloy phase.

[0057] If the negative electrode layer contains a composite alloy consisting of a single Li phase and a Li-M alloy phase as a main component, it may also contain a previously known negative electrode active material. In the present disclosure, the so-called main component refers to a component containing 50% by mass or more when the total mass of the negative electrode layer when the solid battery is fully charged is set to 100% by mass. The negative electrode layer may only contain a composite alloy consisting of a single Li phase and a Li-M alloy phase.

[0058] Examples of negative electrode active materials include metallic lithium (Li) and lithium alloys. Examples of lithium alloys include Li-Au, Li-Mg, Li-Sn, Li-Si, Li-Al, Li-B, Li-C, Li-Ca, Li-Ga, Li-Ge, Li-As, Li-Se, Li-Ru, Li-Rh, Li-Pd, Li-Ag, Li-Cd, Li-In, Li-Sb, Li-Ir, Li-Pt, Li-Hg, Li-Pb, Li-Bi, Li-Zn, Li-Tl, Li-Te, and Li-At.

[0059] The thickness of the negative electrode layer is not particularly limited, but can be 30 nm to 5000 nm when the solid battery is fully charged.

[0060] [Solid electrolyte layer]

[0061] The solid electrolyte layer contains at least a solid electrolyte.

[0062] As the solid electrolyte contained in the solid electrolyte layer, a known solid electrolyte that can be used in a solid battery can be used as appropriate, and examples thereof include oxide-based solid electrolytes and sulfide-based solid electrolytes.

[0063] As sulfide-based solid electrolytes, for example, Li2S-P2S5, Li2S-SiS2, LiX-Li2S-SiS2, LiX-Li2S-P2S5, LiX-Li2O-Li2S-P2S5, LiX-Li2S-P2O5, LiX-Li3PO4-P2S5 and Li3PS4 can be listed. It should be noted that the above-mentioned "Li2S-P2S5" refers to a material made using a raw material composition containing Li2S and P2S5, and the same applies to other records. In addition, the "X" of the above-mentioned LiX represents a halogen element. One or more LiXs may be included in the raw material composition containing the above-mentioned LiX. When two or more LiXs are included, the mixing ratio of the two or more is not particularly limited.

[0064] The molar ratio of each element in the sulfide-based solid electrolyte can be controlled by adjusting the content of each element in the raw material. In addition, the molar ratio and composition of each element in the sulfide-based solid electrolyte can be measured by, for example, ICP emission spectrometry.

[0065] The sulfide-based solid electrolyte may be sulfide glass, crystallized sulfide glass (glass ceramic), or a crystalline material obtained by subjecting a raw material composition to a solid phase reaction treatment.

[0066] The crystal state of the sulfide-based solid electrolyte can be confirmed by, for example, performing powder X-ray diffraction measurement on the sulfide-based solid electrolyte using CuKα rays.

[0067] Sulfide glass can be obtained by subjecting a raw material composition (for example, a mixture of Li2S and P2S5) to amorphization. Examples of amorphization treatment include mechanical polishing.

[0068] Glass ceramics can be obtained by, for example, heat-treating sulfide glass.

[0069] The heat treatment temperature may be higher than the crystallization temperature (Tc) observed by thermal analysis of the sulfide glass, and is usually 195° C. or higher. On the other hand, the upper limit of the heat treatment temperature is not particularly limited.

[0070] The crystallization temperature (Tc) of sulfide glass can be measured by differential thermal analysis (DTA).

[0071] The heat treatment time is not particularly limited as long as it is a time for obtaining the desired crystallinity of the glass ceramics, and is, for example, in the range of 1 minute to 24 hours, particularly in the range of 1 minute to 10 hours.

[0072] The heat treatment method is not particularly limited, and an example thereof includes a method using a sintering furnace.

[0073] Examples of oxide-based solid electrolytes include materials having a garnet-type crystal structure containing Li, La, A (A is at least one of Zr, Nb, Ta, and Al), and O. Examples of oxide-based solid electrolytes include Li 3+x PO 4-x N x (1≦x≦3) etc.

[0074] From the viewpoint of good handling properties, the solid electrolyte may be in the form of particles.

[0075] The average particle size (D50) of the solid electrolyte particles is not particularly limited, but the lower limit may be 0.5 μm or more and the upper limit may be 2 μm or less.

[0076] In the present disclosure, unless otherwise specified, the average particle size of particles is the value of the volume-based median diameter (D50) measured by laser diffraction / scattering particle size distribution measurement. In addition, in the present disclosure, the so-called median diameter (D50) is the diameter (volume average diameter) at which the cumulative volume of particles becomes half (50%) of the total volume when the particles are arranged in order from the smallest particle size.

[0077] As for the solid electrolyte, one kind can be used alone, or two or more kinds can be used. In addition, when using two or more kinds of solid electrolytes, two or more kinds of solid electrolytes can be mixed, or two or more layers of solid electrolytes can be formed to form a multilayer structure.

[0078] The proportion of the solid electrolyte in the solid electrolyte layer is not particularly limited, and may be, for example, 50% by mass or more, 60% by mass or more and 100% by mass or less, 70% by mass or more and 100% by mass or less, or 100% by mass.

[0079] In the solid electrolyte layer, from the viewpoint of showing plasticity, etc., a binder can also be contained. As such a binder, the material exemplified as the binder used in the positive electrode layer described later can be exemplified. However, in order to make it easy to achieve high output, from the viewpoint of preventing excessive aggregation of the solid electrolyte and being able to form a solid electrolyte layer with a uniformly dispersed solid electrolyte, etc., the binder contained in the solid electrolyte layer can be less than 5% by mass.

[0080] The thickness of the solid electrolyte layer is not particularly limited, but is usually 0.1 μm or more and 1 mm or less.

[0081] As a method for forming a solid electrolyte layer, there can be cited a method of press-molding a powder of a solid electrolyte material containing a solid electrolyte, etc. When the powder of the solid electrolyte material is press-molded, a pressing pressure of 1 MPa or more and 600 MPa or less is usually applied.

[0082] The pressurizing method is not particularly limited, and examples of the pressurizing method include those exemplified in the formation of the positive electrode layer described later.

[0083] [positive electrode]

[0084] The positive electrode includes a positive electrode layer and optionally includes a positive electrode current collector.

[0085] [Positive electrode layer]

[0086] The positive electrode layer contains a positive electrode active material, and may contain a solid electrolyte, a conductive material, a binder, and the like as arbitrary components.

[0087] There is no particular restriction on the type of positive electrode active material, and any material that can be used as an active material for a solid battery can be used. In the case where the solid battery is a solid lithium secondary battery, the positive electrode active material can be, for example, metallic lithium (Li), lithium alloys, LiCoO2, LiNi x Co 1-x O2(0<x<1), LiNi 1 / 3 Co 1 / 3Mn 1 / 3 O2, LiMnO2, heterogeneous element substituted Li-Mn spinel, lithium titanate, lithium metal phosphate, LiCoN, Li2SiO3, and Li4SiO4, transition metal oxides, TiS2, Si, SiO2, and lithium storage metal compounds. Heterogeneous element substituted Li-Mn spinel, such as LiMn 1.5 Ni 0.5 O4、LiMn 1.5 Al 0.5 O4、LiMn 1.5 Mg 0.5 O4、LiMn 1.5 Co 0.5 O4、LiMn 1.5 Fe 0.5 O4, and LiMn 1.5 Zn 0.5 O4, etc. Lithium titanate is, for example, Li4Ti5O 12 etc. Examples of lithium metal phosphates include LiFePO4, LiMnPO4, LiCoPO4, and LiNiPO4. Examples of transition metal oxides include V2O5 and MoO3. Examples of lithium storage intermetallic compounds include Mg2Sn, Mg2Ge, Mg2Sb, and Cu3Sb. Examples of lithium alloys include the lithium alloys exemplified as lithium alloys for negative electrode active materials.

[0088] The shape of the positive electrode active material is not particularly limited, and may be in the form of particles.

[0089] A coating layer containing a Li ion conductive oxide can be formed on the surface of the positive electrode active material because the reaction between the positive electrode active material and the solid electrolyte can be suppressed.

[0090] Examples of Li ion conductive oxides include LiNbO3, Li4Ti5O 12 , and Li3PO4, etc. The thickness of the coating is, for example, greater than 0.1 nm, and may be greater than 1 nm. On the other hand, the thickness of the coating is, for example, less than 100 nm, and may be less than 20 nm. The coverage of the coating on the surface of the positive electrode active material is, for example, greater than 70%, and may be greater than 90%.

[0091] As the solid electrolyte, there can be exemplified the solid electrolytes that can be contained in the above-mentioned solid electrolyte layer.

[0092] The content of the solid electrolyte in the positive electrode layer is not particularly limited, and can be, for example, within a range of 1% by mass to 80% by mass, based on 100% by mass of the total mass of the positive electrode layer.

[0093] As the conductive material, known conductive materials can be used, for example, carbon materials and metal particles can be listed. As the carbon material, for example, at least one selected from acetylene black, furnace black, VGCF, carbon nanotubes and carbon nanofibers can be listed. Among them, from the viewpoint of electronic conductivity, it can be at least one selected from VGCF, carbon nanotubes and carbon nanofibers. As metal particles, particles of Ni, Cu, Fe and SUS can be listed.

[0094] The content of the conductive material in the positive electrode layer is not particularly limited.

[0095] Examples of the binder include acrylonitrile butadiene rubber (ABR), butadiene rubber (BR), polyvinylidene fluoride (PVdF), styrene butadiene rubber (SBR), etc. The content of the binder in the positive electrode layer is not particularly limited.

[0096] The thickness of the positive electrode layer is not particularly limited.

[0097] The positive electrode layer can be formed by a conventionally known method.

[0098] For example, the positive electrode active material and other components used as needed are added to a solvent and stirred to prepare a positive electrode layer slurry, which is then applied to one side of a support such as a positive electrode current collector and dried to obtain a positive electrode layer.

[0099] Examples of the solvent include butyl acetate, butyl butyrate, heptane, and N-methyl-2-pyrrolidone.

[0100] The method for coating the positive electrode layer slurry on one side of a support such as a positive electrode current collector is not particularly limited, and examples thereof include doctor blade method, metal mask printing method, electrostatic coating method, dip coating method, spraying method, roll coating method, gravure coating method and screen printing method.

[0101] As the support, any self-supporting support can be appropriately selected and used without particular limitation, and for example, metal foil of Cu, Al, or the like can be used.

[0102] In addition, as another method for forming the positive electrode layer, the powder of the positive electrode mixture containing the positive electrode active material and other components used as needed can be press-formed to form the positive electrode layer. When the powder of the positive electrode mixture is press-formed, a pressing pressure of more than 1 MPa and less than 600 MPa is usually loaded.

[0103] The pressurizing method is not particularly limited, and examples thereof include a method of applying pressure using a plate press, a roll press, and the like.

[0104] [Positive electrode collector]

[0105] Solid batteries generally have a positive electrode current collector that collects current from a positive electrode layer.

[0106] As the positive electrode current collector, a known metal that can be used as a current collector for a solid battery can be used. As such a metal, a metal material containing one or more elements selected from Cu, Ni, Al, V, Au, Pt, Mg, Fe, Ti, Co, Cr, Zn, Ge and In can be exemplified. As the positive electrode current collector, for example, SUS, aluminum, nickel, iron, titanium and carbon can be listed.

[0107] The form of the positive electrode current collector is not particularly limited, and it can be in various forms such as a foil shape and a mesh shape.

[0108] The solid battery includes an outer casing that accommodates a positive electrode layer, a negative electrode layer, a solid electrolyte layer, and the like as necessary.

[0109] The material of the outer casing is not particularly limited as long as it is stable to the electrolyte, and examples thereof include resins such as polypropylene, polyethylene, and acrylic resins.

[0110] The solid battery may be a primary battery or a secondary battery, and the secondary battery may be used. The secondary battery can be repeatedly charged and discharged. The secondary battery can be used as a vehicle battery, for example. In addition, the solid battery may be a solid lithium secondary battery.

[0111] Examples of the shape of the solid battery include a coin shape, a laminate shape, a cylindrical shape, and a square shape.

[0112] As for the manufacturing method of the solid battery disclosed in the present invention, for example, first, the powder of the solid electrolyte material is pressurized to form a solid electrolyte layer. Then, the powder of the positive electrode mixture containing the positive electrode active material is pressurized on one side of the solid electrolyte layer to obtain the positive electrode layer. Then, the powder of the negative electrode material is pressurized on one side of the negative electrode collector to obtain the negative electrode layer. On the surface of the solid electrolyte layer on the opposite side of the surface on which the positive electrode layer is formed, the negative electrode collector-negative electrode layer stack is installed in a manner that the negative electrode layer is connected to the solid electrolyte layer. Then, as needed, the positive electrode collector is installed on the surface of the positive electrode layer on the opposite side of the solid electrolyte layer. In this way, the solid battery disclosed in the present invention can be made.

[0113] In this case, the pressure applied when the negative electrode material powder, the solid electrolyte material powder, and the positive electrode mixture powder are press-molded is usually about 1 MPa or more and 600 MPa or less.

[0114] The pressurizing method is not particularly limited, and the pressurizing methods exemplified in the formation of the positive electrode layer may be mentioned.

[0115] Example

[0116] (Example 1)

[0117] [Anode material]

[0118] As the negative electrode material, a Li-Al composite alloy was prepared by injection molding and then rolled into a composite alloy foil of 100 μm using a roller press. The mass ratio of Al in the Li-Al composite alloy was set to 0.96 mass %, which is equivalent to 0.25 atomic % of Al in the Li-Al composite alloy.

[0119] The surface oxide film of the Li-Al composite alloy foil was removed in a glove box filled with Ar, and the foil was rolled to 80 μm by rollers. Then, the Li-Al composite alloy foil was placed in a dry atmosphere glove box with a dew point of -30°C for 24 hours to obtain a Li-Al composite alloy foil exposed to a dry atmosphere. In addition, as a comparison, a Li-Al composite alloy foil of the same composition was placed in an Ar atmosphere glove box for 24 hours to obtain a Li-Al composite alloy foil exposed to an Ar atmosphere.

[0120] [Evaluation of battery production]

[0121] The following operations were performed in a glove box filled with Ar.

[0122] After exposure to dry atmosphere, the Li-Al composite alloy foil was formed into 1 cm 2 round shape.

[0123] Li2S-P2S5 materials are used in sulfide solid electrolytes. 2 A sulfide-based solid electrolyte powder was placed in a MACOR cell and pressed to obtain a solid electrolyte layer.

[0124] Sulfide composite material powder with a capacity of 4.56 mAh as a positive electrode active material was placed in a McCall chamber and pressed to obtain a positive electrode layer on the solid electrolyte layer.

[0125] The dry atmosphere exposed Li-Al composite alloy foil as the negative electrode material was placed in the McCall chamber to obtain a negative electrode layer on the solid electrolyte layer. The Ni foil as the negative electrode collector was placed on the negative electrode layer in the McCall chamber and pressed. Thus, a pressed powder battery having a positive electrode layer, a solid electrolyte layer, a negative electrode layer, and a negative electrode collector in sequence was obtained.

[0126] The powder compact was restrained with 2 Nm to obtain an evaluation battery A.

[0127] In order to compare the capacity retention rates before and after dry atmosphere exposure, an evaluation battery a was prepared. Evaluation battery a was obtained in the same manner as evaluation battery A except that the Li-Al composite alloy foil after Ar atmosphere exposure was used as the negative electrode material instead of the Li-Al composite alloy foil after dry atmosphere exposure.

[0128] (Example 2)

[0129] As the negative electrode material, a Li-Al composite alloy in which the mass ratio of Al in the Li-Al composite alloy is 3.00 mass % was used. The mass ratio of Al in the Li-Al composite alloy is 3.00 mass %, which is equivalent to 0.79 atomic % of Al in the Li-Al composite alloy. In addition, the same method as in Example 1 was used to obtain an evaluation battery B using a Li-Al composite alloy foil exposed to a dry atmosphere, and further, an evaluation battery B using a Li-Al composite alloy foil exposed to an Ar atmosphere was obtained.

[0130] (Example 3)

[0131] As the negative electrode material, a Li-Al composite alloy in which the mass ratio of Al in the Li-Al composite alloy is 20.16 mass % is used. The mass ratio of Al in the Li-Al composite alloy is 20.16 mass %, which is equivalent to 6.10 atomic % of Al in the Li-Al composite alloy. In addition, the same method as in Example 1 was used to obtain an evaluation cell C using a Li-Al composite alloy foil exposed to a dry atmosphere, and further, an evaluation cell c using a Li-Al composite alloy foil exposed to an Ar atmosphere was obtained.

[0132] (Example 4)

[0133] As the negative electrode material, a Li-In composite alloy was used. A Li-In composite alloy in which the mass ratio of In in the Li-In composite alloy was 0.99 mass % was used. The mass ratio of In in the Li-In composite alloy was 0.99 mass %, which was equivalent to an atomic % of In in the Li-In composite alloy of 0.06 atomic %. In addition, an evaluation cell D using a Li-In composite alloy foil exposed to a dry atmosphere was obtained by the same method as in Example 1, and an evaluation cell d using a Li-In composite alloy foil exposed to an Ar atmosphere was obtained.

[0134] (Example 5)

[0135] As the negative electrode material, a Li-In composite alloy was used. A Li-In composite alloy in which the mass ratio of In in the Li-In composite alloy was 3.00 mass % was used. The mass ratio of In in the Li-In composite alloy was 3.00 mass %, which is equivalent to an atomic % of In in the Li-In composite alloy of 0.19 atomic %. In addition, an evaluation cell E using a Li-In composite alloy foil exposed to a dry atmosphere was obtained by the same method as in Example 1, and an evaluation cell e using a Li-In composite alloy foil exposed to an Ar atmosphere was obtained.

[0136] (Example 6)

[0137] As the negative electrode material, a Li-In composite alloy was used. A Li-In composite alloy in which the mass ratio of In in the Li-In composite alloy was 10.00 mass % was used. The mass ratio of In in the Li-In composite alloy was 10.00 mass %, which was equivalent to an atomic % of In in the Li-In composite alloy of 0.67 atomic %. In addition, an evaluation cell F using a Li-In composite alloy foil exposed to a dry atmosphere was obtained by the same method as in Example 1, and an evaluation cell f using a Li-In composite alloy foil exposed to an Ar atmosphere was obtained.

[0138] (Example 7)

[0139] As the negative electrode material, a Li-In composite alloy was used. A Li-In composite alloy in which the mass ratio of In in the Li-In composite alloy was 20.02 mass % was used. The mass ratio of In in the Li-In composite alloy was 20.02 mass %, which was equivalent to an atomic % of In in the Li-In composite alloy of 1.50 atomic %. In addition, an evaluation cell G using a Li-In composite alloy foil exposed to a dry atmosphere was obtained by the same method as in Example 1, and an evaluation cell g using a Li-In composite alloy foil exposed to an Ar atmosphere was obtained.

[0140] (Example 8)

[0141] As the negative electrode material, a Li-Zn composite alloy was used. A Li-Zn composite alloy in which the mass ratio of Zn in the Li-Zn composite alloy was 0.93 mass % was used. The mass ratio of Zn in the Li-Zn composite alloy was 0.93 mass %, which was equivalent to an atomic % of Zn in the Li-Zn composite alloy of 0.10 atomic %. In addition, an evaluation cell H using a Li-Zn composite alloy foil exposed to a dry atmosphere was obtained by the same method as in Example 1, and an evaluation cell h using a Li-Zn composite alloy foil exposed to an Ar atmosphere was obtained.

[0142] (Example 9)

[0143] As the negative electrode material, a Li-Zn composite alloy was used. A Li-Zn composite alloy in which the mass ratio of Zn in the Li-Zn composite alloy was 3.00 mass % was used. The mass ratio of Zn in the Li-Zn composite alloy was 3.00 mass %, which was equivalent to an atomic % of Zn in the Li-Zn composite alloy of 0.33 atomic %. In addition, an evaluation cell I using a Li-Zn composite alloy foil exposed to a dry atmosphere was obtained by the same method as in Example 1, and an evaluation cell i using a Li-Zn composite alloy foil exposed to an Ar atmosphere was obtained.

[0144] (Example 10)

[0145] As the negative electrode material, a Li-Zn composite alloy was used. A Li-Zn composite alloy in which the mass ratio of Zn in the Li-Zn composite alloy was 10.27 mass % was used. The mass ratio of Zn in the Li-Zn composite alloy was 10.27 mass %, which was equivalent to an atomic % of Zn in the Li-Zn composite alloy of 1.20 atomic %. In addition, an evaluation cell J using a Li-Zn composite alloy foil exposed to a dry atmosphere was obtained by the same method as in Example 1, and an evaluation cell j using a Li-Zn composite alloy foil exposed to an Ar atmosphere was obtained.

[0146] (Comparative Example 1)

[0147] An evaluation cell K using a Li foil exposed to a dry atmosphere was obtained in the same manner as in Example 1 except that Li was used as the negative electrode material. Furthermore, an evaluation cell k using a Li foil exposed to an Ar atmosphere was obtained.

[0148] [Discharge evaluation of evaluation battery]

[0149] The evaluation battery A was placed in a removable flask and sealed. The evaluation battery A was placed in a 60°C constant temperature chamber for 3 hours to make the temperature inside the evaluation battery A uniform. Then, the evaluation battery A was charged with a current density of 0.1C (0.456 mAh / cm 2 ) constant current discharge, and the discharge was stopped when the voltage of evaluation battery A reached 2 V. Thus, the dry atmosphere exposure discharge capacity (mAh / cm 2 ).

[0150] Evaluation battery a was discharged in the same manner as evaluation battery A, and the Ar atmosphere exposure discharge capacity (mAh / cm 2 ). The dry atmosphere exposure capacity retention rate was calculated from the dry atmosphere exposure discharge capacity and the Ar atmosphere exposure discharge capacity according to the following formula. The results are shown in Table 1.

[0151] Dry atmosphere exposure capacity maintenance rate (%) = 100 × (dry atmosphere exposure discharge capacity ÷ Ar atmosphere exposure discharge capacity)

[0152] Evaluation Batteries B to K and Evaluation Batteries b to k were also discharged in the same manner as Evaluation Batteries A and Evaluation Batteries a, and the dry atmosphere exposure capacity retention rates were calculated.

[0153]

Table 1

[0154]

[0155] [Evaluation results]

[0156] In the evaluation battery using the Li foil of Comparative Example 1, the dry atmosphere exposure capacity maintenance rate was 22%.

[0157] On the other hand, in the evaluation cells using the composite alloy foil of Examples 1 to 10, the dry atmosphere exposure capacity maintenance rate was improved compared to the evaluation cell using the Li foil.

[0158] When M of the composite alloy is Al, the dry atmosphere exposure capacity maintenance rate is the maximum, 100%, when the composite alloy contains 6.10 atomic % of Al.

[0159] When M of the composite alloy is In, the dry atmosphere exposure capacity maintenance rate becomes the maximum, 100%, when the composite alloy contains 0.67 atomic % of In.

[0160] When M of the composite alloy is Zn, the dry atmosphere exposure capacity maintenance rate becomes the maximum at 90% when the composite alloy contains 0.10 atomic % of Zn.

[0161] Figure 5 This is an example of a discharge curve of the evaluation battery C using the Li-Al composite alloy as the negative electrode in Example 3. Figure 1 The phase diagram of Li contains a small amount of Li9Al4 as a Li-Al alloy phase. Figure 5 As shown in the figure, Li9Al4 has a potential 0.6 V lower than Li. + Since charging and discharging are performed at a potential at which Li is desorbed, Li9Al4 does not contribute to charging and discharging within a capacity range of 2000 mAh / g.

[0162] Figure 6 This is an example of a discharge curve of the evaluation battery F using the Li-In composite alloy as the negative electrode in Example 6. Figure 2The phase diagram of Li contains a small amount of InLi as a Li-In alloy phase. Figure 6 As shown in the figure, the reaction potential from In is not observed due to the small amount of In. + Charging and discharging are performed at a potential at which Li is separated, and InLi does not contribute to charging and discharging.

[0163] Figure 7 This is an example of a discharge curve of the evaluation battery H using the Li-Zn composite alloy as the negative electrode of Example 8. Figure 3 The phase diagram of Li contains a small amount of LiZn as a Li-Zn alloy phase. Figure 7 As shown in the figure, the reaction potential from Zn is not observed due to the small amount of Zn. + The charge and discharge are performed at a potential at which Li is separated, and LiZn does not contribute to the charge and discharge.

[0164] Description of Reference Numerals

[0165] 11. Negative electrode collector

[0166] 12 Solid electrolyte layer

[0167] 13. Positive electrode layer

[0168] 14. Positive electrode collector

[0169] 15 Negative electrode layer

[0170] 100 Solid State Battery

Claims

1. A solid battery is a solid battery that uses the precipitation-dissolution reaction of lithium metal as a negative electrode reaction, characterized in that: The invention relates to a solid battery comprising: a positive electrode including a positive electrode layer, a negative electrode including a negative electrode collector and a negative electrode layer, and a solid electrolyte layer arranged between the positive electrode layer and the negative electrode layer, wherein the negative electrode layer includes a negative electrode material, the negative electrode material is a composite alloy composed of a single Li phase and a Li-M alloy phase, the M contained in the Li-M alloy phase is Zn, when the solid battery is fully charged, the content ratio of the M in the composite alloy is 0.90 mass % or more and 21.00 mass % or less, and the composite alloy contains at least 0.10 atomic % or more and 0.33 atomic % or less of Zn as the M, The positive electrode layer contains a positive electrode active material. A coating layer containing a Li ion conductive oxide is formed on the surface of the positive electrode active material.

Citation Information

Patent Citations

  • Negative electrode for all-solid-state secondary battery and all-solid-state secondary battery

    JP2018129159A

  • All-solid battery, and method for manufacturing the same

    JP2020009619A

  • Lithium air battery based on a lithium alloy negative electrode

    CN109698396A

  • Lithium metal alloy negative electrode material and preparation method and application thereof

    CN110120502A